Co-presentation of diabetic ketoacidosis and hepatitis an infection with anasarca: a case report - Ranabijuli, Pradeep Kumar; A., Nazparveen L.; Sitaram, Arangale Pankaj; Kamble, Komal (International Journal of Contemporary Pediatrics, 2025)
Diabetic ketoacidosis is the common initial presentation of Type 1 Diabetes Mellitus in paediatric practice. Hepatitis A infection is a common cause of jaundice in children with varied constitutional symptoms. However, co-presentation of diabetic ketoacidosis and hepatitis A infection with anasarca is rare. One four-year-ten-month-old male child presented to the emergency department of our hospital with diabetic ketoacidosis with new-onset Type 1 diabetes mellitus. At the time of presentation, the blood sugar level was in the diabetic range, 677 mg% laboratory value and was suggestive of diabetes mellitus. The HbA1c level was 14.47% at that time; however, there was no history of the classical triad of polyuria, polydipsia and polyphagia in the child. The child presented with mild acidosis (pH 7.3) and responded to the Milwaukee regimen of DKA management. During the course of the management, the child developed clinical jaundice on the 5th day of hospital admission and was investigated and diagnosed as having viral hepatitis A. On the 7th day of illness, the child developed anasarca in the form of moderate pleural effusion and gross ascites, leading to respiratory distress along with pedal edema and scrotal edema. The anasarca responded to symptomatic treatment and the clinical improvement of Hepatitis A occurred after 15 days. The stressful event of brewing hepatitis A, precipitating DKA in a relatively asymptomatic child of type 1 diabetes mellitus, is more likely in our case. The chance association of both the conditions in an underweight child with a history of 3rd degree consanguinity is noted in our child. The child also developed anasarca, which is uncommon in viral hepatitis A or diabetic ketoacidosis alone.